A field test of a simplified method of estimating circadian stimulus. (August 2022) - Babilon, S; Beck, S; Khanh, TQ
Residents of nursing homes often have a very limited access to natural daylight, which is the main environmental cue for circadian entrainment that usually cannot be compensated by standard indoor lighting. For the development of adequate modernization strategies with regard to a more human-centred lighting approach, reliable field measurements of the circadian effectiveness of the prevalent lighting conditions are required. To ease the task for the lighting practitioner, our lab recently developed a simplified method of estimating the biologically meaningful circadian stimulus (CS) metric using standard measurement equipment. In this work, the proposed method is applied for the first time in field measurements to assess the circadian effectiveness of the indoor light conditions including daylight entry of a nursing home in the Frankfurt Rhine-Main area. Reference thresholds for low, moderate and high circadian stimuli derived from the literature were used for subsequent data analysis. Mostly, moderate to rather low CS values were found. It is concluded that the amount of circadian-effective light is insufficient to provoke proper circadian stimulation, which may lead to progressive circadian disruptions manifesting in adverse effects on the residents' health and well-being. Further evidence is provided that the insufficient-lighting-situation in nursing homes is a serious problem in long-term care and needs urgent consideration in health policy.